Diagnosis of rotor faults by fast Fourier transform using an auxiliary winding voltage - Yakout Khadouj Jelbaoui; Lamiaa El Menzhi; Abdallah Saad (Institute of Advanced Engineering and Science, 2021)
Condition monitoring and on-line detection have attracted several researchers in order to carry out an efficient diagnosis of machine failures. Therefore, the detection in early stage avoids system breakdown and reduce the maintenance cost. This paper presents a new diagnosic approach to detect the broken bars and broken end ring faults for a squirrel cage induction machine based on the fast Fourier transform analysis applied on a new signature as the voltage of an auxiliary winding. The auxiliary winding is a small coil inserted between two of the stator phases, the explicit expression of its voltage is presented. The signal is monitored in six faults cases under a different load level, the emergence of the fault frequencies changes for each kind of failure. The successfully simulation results obtained show the effectiveness of this approach.